Nitrogen addition aggravates microbial carbon limitation: Evidence from ecoenzymatic stoichiometry - Chen, Hao; Li, Dejun; Zhao, Jie; Zhang, Wei; Xiao, Kongcao; Wang, Kelin (Geoderma, 2018)
Nitrogen (N) deposition may change carbon (C) or nutrient limitation of soil microbes, but whether such change can be reflected by ecoenzymatic stoichiometry has not been well studied. Here, we synthesized data from 36 published studies to evaluate the responses of ecoenzymatic stoichiometry to N addition. Results showed that N addition did not change the enzyme ratio (1:1:1) of C, N, and phosphorus (P) acquisition, and also did not change vector angle of ecoenzymatic stoichiometry which is an indicator of microbial P limitation. However, N addition increased two indicators of C-limitation significantly (i.e., activity of β-D-glucosidase and vector length), both of which indicated that N addition aggravated microbial C-limitation. The aggravated C-limitation may be partly due to the reduced decomposition of recalcitrant organic C. Our study extends our understanding of the effects of N deposition on C cycling from a new perspective. •A meta-analysis was conducted by collecting 36 published studies.•Changes of microbial resource limitation after N addition were addressed.•N input aggravated C-limitation due to reduced recalcitrant C decomposition.•N addition did not affect soil microbial P-limitation.